PENGARUH PENDIDIKAN KESEHATAN MINUM OBAT TERHADAP KEPATUHAN MINUM OBAT PASIEN TUBERKULOSIS DIWILAYAH PUSKESMAS SALIBABU - Vani Y Tampilang; Thirsa O Mongi; Marice Tatulus (Yayasan Syalom Cipta Sumikolah, 2025)
This study is a quantitative study that uses a Quasi-experimental research design type. The research design used was One-Group Pre-Post test Design, the time was in December 2024 and the research location was at the Tateli Health Center, Mandolang District, Minahasa Regency. The sampling technique used a total population of 23. The statistical test used was the